RISK FACTORS ASSOCIATED WITH BOTH BLOOD AND INTERNAL PARASITES IN DAIRY FARMS IN KUKU AREA, KHARTOUM STATE - ALWathig Ahmed, Mohamed; Elamin Abdelgadir, Atif; Hassan Elmalik, Khitma (Journal of Veterinary Medicine and Animal Production, 2022)
Investigation of blood and internal parasites among different seasons (dry cool, dry hot and wet hot) in dairy herds in Kuku area of Khartoum State, revealed that there was a high prevalence of blood parasites in the dry cool season (46%) compared to dry hot and wet hot season (14.74% and 5.68%, respectively). While the presence of internal parasite was found to be less than infection with blood parasites (15%, 8.42% and 11.36 for dry cool, dry hot and wet hot season, respectively). A positive association (χ 2 =48.483, P<0.01) was found between season and presence of blood parasites and season is considered to be a protective factor (OR= 0.244). In contrast, presence of internal parasites was not associated with season (χ 2 = 2.058, P>0.05). Tick infestation was found statistically significant (χ 2 = 20.583, P<0.01) with respect to presence of blood parasites and could be a risk factor (OR=3.586). Packed cell volume (PCV) was found strongly associated with both blood and internal parasites (χ 2 = 9.679 &6.573 P<0.01, respectively